Current transport mechanism and photovoltaic properties of photoelectrochemical cells of ITO/TiO2/PVC-LiClO4/graphite - Rahman M.Y.A. (2023)
This paper deals with the current transport mechanism of solid state photoelectrochemical cells of ITO/TiO2/PVC-LiClO4/graphite as well as the physical properties of a component of a device affecting its performance. The principle of operation and a schematic energy level diagram for the materials used in the photoelectrochemical cells are presented. The device makes use of ITO films, TiO2 films, PVC-LiClO4 and graphite films as photoanode, photovoltaic material, solid electrolyte and counter electrode, respectively. The device shows rectification. The Jsc and Voc obtained at 100 mW cm-2 were 0.95 ?Acm-2 and 180 mV, respectively. 2006 Elsevier B.V. All rights reserved.